Patterns of coastal resources utilization among the fisherfolk in Brgy. Sta. Rita, San Joaquin, Iloilo. - Custodio, Julius Rey; Natan, Celza (2010.)
The study aims to describe the pattern of coastal utilization of fisherfolk in a village in San Joaquin, Iloilo. It has the following specific objectives: to identify what resources are available in the coastal area; to determine how fisherfolk utilize the resources in the coastal area; to identify the pattern of resource utilization based on fisherfolk's gender; and to know the beliefs and practices of fisher folk in relation to the coastal environment., The researchers used the census in gathering the data. The sample size of this study is fifty fishermen-husbands with ages ranging from 25 to 52 years old. the data was gathered using an interview schedule and analyzed using simple frequency counts and percentages. The study suggests that men and women are utilizing the resources in the coastal area differently. Men utilized the resources off shore since they are the one who are directly exposed. Women utilized more of the resources onshore. The pattern utilization is also affected by the beliefs and practices of the fisher folk. Thus, the study concludes that there are many resources found in the coastal area, the commonly mentioned are the fish, lumber, tree trunks/branches, coconut fruits, coconut leaves, coconut branch, sand and stone. Utilization of these resources varies according to gender, which means that men have different ways of utilization with that of the women. also, beliefs and practices of fisherfolk influence their pattern of utilization in such a way that they were able to preserve some part of coastal area. For the improvement of the study, the researchers recommend that sample size should be increased. A comparative study that will cover other fishing communities is also recommended.
Thesis (Undergraduate, Bachelor of Arts in Sociology) College of Arts and Sciences, University of the Philippines in the Visayas, Miagao, Iloilo.
Keywords: Fisherfolks -- Brgy. Sta. Rita, San Joaquin -- Iloilo